PIK3CA-mediated PI3-kinase signalling is essential for HPV-induced transformation in vitro - Henken, Florianne E (BioMed Central, 2011)
BACKGROUND: High-risk human papillomavirus (hrHPV) infections are causally related to cervical cancer development. The additional (epi)genetic alterations driving malignant transformation of hrHPV-infected cells however, are not yet fully elucidated. In this study we experimentally assessed the role of the PI3-kinase pathway and its regulator PIK3CA, which is frequently altered in cervical cancer, in HPV-induced transformation. METHODS: Cervical carcinomas and ectocervical controls were assessed for PIK3CA mRNA and protein expression by quantitative RT-PCR and immunohistochemical staining, respectively. A longitudinal in vitro model system of hrHPV-transfected keratinocytes, representing the immortal and anchorage independent phenotype, was assayed for PI3-kinase activation and function using chemical pathway inhibition i.e. LY294002 treatment, and PIK3CA RNA interference. Phenotypes examined included cellular viability, migration, anchorage independent growth and differentiation. mRNA expression of hTERT and HPV16 E6E7 were studied using quantitative RT-PCR and Northern blotting. RESULTS: Cervical carcinomas showed significant overexpression of PIK3CA compared to controls. During HPV-induced transformation in vitro, expression of the catalytic subunit PIK3CA as well as activation of downstream effector PKB/AKT progressively increased in parallel. Inhibition of PI3-kinase signalling in HPV16-transfected keratinocytes by chemical interference or siRNA-mediated silencing of PIK3CA resulted in a decreased phosphorylation of PKB/AKT. Moreover, blockage of PI3-kinase resulted in reduced cellular viability, migration, and anchorage independent growth. These properties were accompanied with a downregulation of HPV16E7 and hTERT mRNA expression. In organotypic raft cultures of HPV16- and HPV18-immortalized cells, phosphorylated PKB/AKT was primarily seen in differentiated cells staining positive for cytokeratin 10 (CK10). Upon PI3-kinase signalling inhibition, there was a severe impairment in epithelial tissue development as well as a dramatic reduction in p-PKB/AKT and CK10. CONCLUSION: The present data indicate that activation of the PI3-kinase/PKB/AKT pathway through PIK3CA regulates various transformed phenotypes as well as growth and differentiation of HPV-immortalized cells and may therefore play a pivotal role in HPV-induced carcinogenesis.